Glycoside Hydrolases and Glycosyltransferases from Hyperthermophilic Archaea: Insights on Their Characteristics and Applications in Biotechnology - Khadija Amin (MDPI AG, 2021)
Hyperthermophilic Archaea colonizing unnatural habitats of extremes conditions such as volcanoes and deep-sea hydrothermal vents represent an unmeasurable bioresource for enzymes used in various industrial applications. Their enzymes show distinct structural and functional properties and are resistant to extreme conditions of temperature and pressure where their mesophilic homologs fail. In this review, we will outline carbohydrate-active enzymes (CAZymes) from hyperthermophilic Archaea with specific focus on the two largest families, glycoside hydrolases (GHs) and glycosyltransferases (GTs). We will present the latest advances on these enzymes particularly in the light of novel accumulating data from genomics and metagenomics sequencing technologies. We will discuss the contribution of these enzymes from hyperthermophilic Archaea to industrial applications and put the emphasis on newly identifed enzymes. We will highlight their common biochemical and distinct features. Finally, we will overview the areas that remain to be explored to identify novel promising hyperthermozymes.